Digital Radiographic Evaluation of the Level of Alveolar Bone Crest in External Hexagon Implants Submitted to 2 Types of Implant Abutments Under Immediate Loading - Ponzoni, Daniela [UNESP]; Gadotti, Rodrigo Juliano; de Mattias Sartori, Ivete Aparecida; Liotto, Elirio Mario (Lippincott Williams & Wilkins, 2011)
Purpose: The aim of this study was to evaluate by means of digital radiography the behavior of the alveolar bone crest in external hexagon implants following the use of 2 different types of abutments, one for conventional cemented prosthesis and one for modified cemented prosthesis.Methods: Ten external hexagon implants (platform 4.1) were placed in 5 patients. Initial instrumentation was carried out to obtain primary stability of the temporary prostheses under immediate loading. Each patient received both abutments for conventional and modified cemented prosthesis. Standardized digital periapical radiographies were performed at times T0 (immediately after implant placement) and T1 (4 months after implant placement). A straight line was initially established from the implant platform to the distal and mesial periimplantar marginal bone tissue (immediately in contact with the implant) and measured by digital radiography, using Sidexis version 2.3 (Sirona Dental Systems GmbH, Bensheim, Germany) software. The data were submitted to paired-samples t-test analysis.Results: There was no significant difference between the conventional and modified cemented prosthesis. In both cases, t-test results were within the null hypothesis level.Conclusion: The abutment for the modified cemented prosthesis resulted in no significant radiographic difference of alveolar bone crest height, when compared with the conventional cemented prostheses.
Keywords: Dental implants; oral rehabilitation; prosthesis